Investigating the link between frailty and outcomes in geriatric patients with isolated rib fractures - Yang Cao; Shahin Mohseni; Babak Sarani; Frank Hildebrand; Ahmad Mohammad Ismail; Maximilian Peter Forssten; Marcelo AF Ribeiro (Trauma Surgery & Acute Care Open)
Background Studies have shown an increased risk of morbidity in elderly patients suffering rib fractures from blunt trauma. The association between frailty and rib fractures on adverse outcomes is still ill-defined. In the current investigation, we sought to delineate the association between frailty, measured using the Orthopedic Frailty Score (OFS), and outcomes in geriatric patients with isolated rib fractures.Methods All geriatric (aged 65 years or older) patients registered in the 2013–2019 Trauma Quality Improvement database with a conservatively managed isolated rib fracture were considered for inclusion. An isolated rib fracture was defined as the presence of ≥1 rib fracture, a thorax Abbreviated Injury Scale (AIS) between 1 and 5, an AIS ≤1 in all other regions, as well as the absence of pneumothorax, hemothorax, or pulmonary contusion. Based on patients’ OFS, patients were classified as non-frail (OFS 0), pre-frail (OFS 1), or frail (OFS ≥2). The prevalence ratio (PR) of composite complications, in-hospital mortality, failure-to-rescue (FTR), and intensive care unit (ICU) admission between the OFS groups was determined using Poisson regression models to adjust for potential confounding.Results A total of 65 375 patients met the study’s inclusion criteria of whom 60% were non-frail, 29% were pre-frail, and 11% were frail. There was a stepwise increased risk of complications, in-hospital mortality, and FTR from non-frail to pre-frail and frail. Compared with non-frail patients, frail patients exhibited a 87% increased risk of in-hospital mortality [adjusted PR (95% CI): 1.87 (1.52-2.31), p<0.001], a 44% increased risk of complications [adjusted PR (95% CI): 1.44 (1.23-1.67), p<0.001], a doubling in the risk of FTR [adjusted PR (95% CI): 2.08 (1.45-2.98), p<0.001], and a 17% increased risk of ICU admission [adjusted PR (95% CI): 1.17 (1.11-1.23), p<0.001].Conclusion There is a strong association between frailty, measured using the OFS, and adverse outcomes in geriatric patients managed conservatively for rib fractures.